SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-2162
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Injection Strategy Investigation for Well-Mixed Operation in an Optical Wall-Guided Spark-Ignition Direct-Injection (WG-SIDI) Engine through Flame Shape Analysis

Abstract: One major drawback of spark-ignition direct-injection (SIDI) engines is increased particulate matter (PM) and unburned hydrocarbon emissions at high load, due to wall wetting and a reduction in available air/fuel mixing time when compared to port-fuel injection (PFI). It is therefore necessary to understand the mechanics behind injection strategies which are capable of reducing these emissions while also maintaining the performance and efficiency of the engine. This study investigates the effect of varying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It was also reported that the flame front grew in a more spherical manner, although the extent of this phenomenon was not quantified. Previous work conducted by the present authors found that a double injection strategy resulted in higher indicated performance and flame propagation speeds when compared to an equivalent single injection strategy [29]. The application of a best-fit ellipse algorithm to the flame boundary points revealed that double injections also gave rise to more circular flames, thought to be due to increased charge homogeneity resulting in less variation in laminar burn speed throughout the combustion chamber.…”
Section: Introductionmentioning
confidence: 45%
“…It was also reported that the flame front grew in a more spherical manner, although the extent of this phenomenon was not quantified. Previous work conducted by the present authors found that a double injection strategy resulted in higher indicated performance and flame propagation speeds when compared to an equivalent single injection strategy [29]. The application of a best-fit ellipse algorithm to the flame boundary points revealed that double injections also gave rise to more circular flames, thought to be due to increased charge homogeneity resulting in less variation in laminar burn speed throughout the combustion chamber.…”
Section: Introductionmentioning
confidence: 45%
“…The selection of recording 105 individual cycles is based on careful trial-and error testing such that the processed flame and in-cylinder pressure parameters are effectively isolated from the cyclic variation. A similar approach is found in the previous work conducted in the same optical engine [13]. The flame images were processed by in-house developed Matlab codes, which employ contrast adjustment, imaging binarization and boundary detection processes.…”
Section: Image Capture and Post-processingmentioning
confidence: 99%
“…The flame images were processed by in-house developed Matlab codes, which employ contrast adjustment, imaging binarization and boundary detection processes. The area of the flame was calculated from the binarized image in each frame, which was used to estimate the flame growth rate [13].…”
Section: Image Capture and Post-processingmentioning
confidence: 99%
“…PFI: port fuel injection; CA aTDC: Crank-Angle There are a number of diagnostics that one can use to observe the flame, ranging from simple natural emission based such as chemiluminescence or natural-flame luminosity to more complicated techniques such as tomography of hydroxyl planar laser-induced fluorescence (OH PLIF). Clark et al investigated the effect of the timing of the first and second injection for an evenly split dual injection strategy in an optical engine [10,11]. Performance parameters derived from in-cylinder pressure data are analyzed alongside high-speed natural flame luminescence images in order to obtain relationships between engine output and the physical properties associated with flame propagation.…”
Section: Engine Specifications and Operating Conditionsmentioning
confidence: 99%